Innovative Packaging for Wine - Cezar Ionuț BICHESCU; Dimitrie STOICA; Angela Stela IVAN; Maricica STOICA (ACROSS)
The wine packaging industry is evolving rapidly, driven by technological advancements, sustainability concerns, and consumer preferences. Classic glass bottles, while still predominant, are being supplemented by innovative packaging such as Bag-in-Box, cans, polymer/biopolymer-based bottles, single-serve pouches, and kegs. These alternatives offer some benefits like lower carbon footprints and enhanced convenience, although they also face challenges related to consumer perception and acceptance. Smart packaging enhances wine quality preservation by controlling oxygen levels and monitoring product freshness, thereby extending shelf life and ensuring safety. Recent trends indicate a growing demand for eco-friendly and aesthetically innovative packaging solutions, aligning with consumer preferences and emphasising the industry's dynamic nature and potential for continued growth. This paper offers an overview of different innovative wine packaging.